Understanding of nutrition information on food labels among higher income adults in India. (June 2023) - Mediratta, Srishti; Mathur, Pulkit
Objectives: This study assessed food label reading habits and understanding of nutrition information on food labels by higher income adults in India. Design: It involved a cross-sectional study using non-probability purposive sampling. Setting: Data were collected by mixed methods approach between March 2019 and February 2020. Adults were selected from housing colonies in four geographical zones of Delhi, India. Method: A total of 589 adults (20–40 years) belonging to upper middle-income and high-income groups were selected. Associations between gender, family income, age, marital status, and label reading habits were assessed using Chi-square tests. Demographic predictors of food label reading habits were identified using binary logistic regression with a level of significance set at p  < .05. Results: Participants read the food labels (79%) and noticed the nutrient claims (76%) on food labels. Female participants were more likely to understand nutrition information as compared with male participants (odds ratio [OR] = 1.52, p  = .04). Female participants were also more likely to notice the nutrient claims on the packet of food products (OR = 1.99, p  < .01) as compared with male participants. The majority of participants found the 'traffic light scheme' format easy to understand. Conclusion: Consumers look for nutrition information on food labels. They value healthier food alternatives but most are unable to decipher the nutrition labels. Food labels should communicate the healthfulness of products in a straightforward manner to enable better food choices.